Efeitos da reposição com insulina nas disfunções cardiometabólicas induzidas pelo diabetes experimental por estreptozotocina - Freitas, Sarah Cristina Ferreira (2016)
Studies show that people with type 1 diabetes presented increased cardiovascular mortality risk compared to normoglycemic, even when kept under good glycemic control. However, the mechanisms involved in this condition are not well understood. The model of diabetes by streptozotocin (STZ) has extensively been used for the study of chronic complications of diabetes, but usually the animals are kept without insulin replacement and therefore with very high glucose levels. Thus, the objective of this study was to evaluate the effects of insulin replacement therapy on cardiac, autonomic and oxidative stress (OS) parameters in a model of type 1 DM induced by STZ. For this, Wistar rats (230-260g) were divided into 3 groups (n=8/group): control (C), diabetic (D, streptozotocin 50mg/kg), and diabetic treated daily with insulin (2U morning and 4U afternoon, sc) (DTI). Blood glucose was measured weekly. Metabolic cage evaluations were performed on 15 and 30 days of protocol. At 30 days of protocol, the cardiac function was assessed by echocardiography. On the day before, the animals were cannulated and baroreflex sensitivity and cardiac autonomic tone were evaluated, as well as cardiovascular autonomic modulation. The EO analysis were performed in the cardiac and renal tissues. The diabetic groups showed hyperglycemia (>350mg/dL) at the beginning of the protocol. Insulin therapy normalized glycaemia, as well as polyuria, polydipsia, and polyphagia observed in D group. There was a reduction in left ventricular mass in D group and this change was not observed in the DTI group. There was impairment of systolic function (fractional shortening) in D group that was reversed with insulin treatment (DTI). Regarding diastolic function, the corrected isovolumetric relaxation time was increased and the E/A ratio was reduced in D and DTI groups compared to C group. Treatment with insulin normalized arterial pressure (AP), heart rate (HR), the intrinsic HR and vagal and sympathetic tone and HR variability that were impaired in D group. The baroreflex sensitivity, for bradycardic and tachycardic responses, and the systolic AP variability were impaired in D compared to C group. The dysfunction in tachycardic response and in AP variability has not been normalized by treatment with insulin. In the OS analysis, D group had more oxidized and reduced glutathione in the heart and increased lipid peroxidation in cardiac and renal tissues, which were not observed in the insulin-treated group. Our findings confirm metabolic, cardiovascular and autonomic dysfunctions, and changes in renal tissue, in STZ induceddiabetic rats. These changes were partially attenuated by treatment with insulin for 30 days.. However, the most important result observed was that the insulin treatment was not able to reverse the dysfunctions in cardiac diastole, baroreflex and systolic AP variability, suggesting a remaining cardiovascular risk even under good glycemic control in this experimental model of type 1 diabetes.